The Trade-Off between Enteric and Manure Methane Emissions and Their Bacterial Ecology in Lactating Cows Fed Diets Varying in Forage-to-Concentrate Ratio and Rapeseed Oil - Darabighane, Babak; Tapio, Ilma; Rasi, Saija; Seppänen, Ari-Matti; Blasco, Lucia; Ahvenjärvi, Seppo; Bayat, Ali R. (MDPI, 2024)
An experiment was conducted to examine how dietary interventions reducing enteric methane (CH4) emissions influence manure CH4 emissions in biogas production (as biochemical methane potential (BMP)) or under static conditions mimicking natural manure storage conditions. Experimental treatments consisted of a factorial arrangement of high (HF: 0.65) or low (LF: 0.35) levels of forage and 0 or 50 g of rapeseed oil per kg of diet dry matter. Oil supplementation reduced daily enteric CH4 emissions, especially in the HF diet, by 20%. Greater dietary concentrate proportion reduced CH4 yield and intensity (6 and 12%, respectively) and decreased pH, increased total volatile fatty acids, and molar proportions of butyrate and valerate in feces incubated under static conditions. Oil supplementation increased daily BMP and BMP calculated per unit of organic matter (OM) (17 and 15%, respectively). Increased dietary concentrate had no impact on daily BMP and BMP per unit of OM, whereas it reduced daily CH4 production by 89% and CH4 per unit of OM by 91% under static conditions. Dietary oil supplementation tended to decrease fecal CH4 production per unit of digestible OM (23%) under static conditions. Diets had no impact on the alpha diversity of ruminal prokaryotes. After incubation, the fecal prokaryote community was significantly less diverse. Diets had no effect on alpha diversity in the BMP experiment, but static trial fecal samples originating from the HF diet showed significantly lower diversity compared with the LF diet. Overall, the tested dietary interventions reduced enteric CH4 emissions and reduced or tended to reduce manure CH4 emissions under static conditions, indicating a lack of trade-off between enteric and manure CH4 emissions. The potential for increasing CH4 yields in biogas industries due to dietary interventions could lead to a sustainable synergy between farms and industry.
Keywords: enteric methane; manure methane; trade-off; microbial community; dietary intervention